FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA PENGGUNA MARKETPLACE DI BANDAR LAMPUNG - Candra, Dwi; Wardianto, K Bagus; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine the effects of price perception, sales promotion, product quality, and product reviews on purchasing decisions in the marketplace. The explanatory research was used as the research type through a quantitative approach. The sampling technique used purposive sampling with a total sample of 100 respondents. The data were obtained from questionnaires using Likert scale. Data analysis techniques of this study used descriptive analysis and multiple linear regression analysis through SPSS 25. Based on the results of the study showed that there is a partially variable perception of price, sales promotion, product quality, and product reviews on purchasing decisions. Furthermore, simultaneously price perception, sales promotion, product quality, and product reviews also have a significant effect on purchasing decisions in the marketplace. Then, the R2 test research showed that 44,4% of purchasing decisions were affected by pric perception, sales promotion, product quality, and product reviews, and the remaining of 55,6% purchasing decisions were influenced by other variables. Key Words : Price Perception, Sales Promotion, Product Quality, Product Reviews, Purchase Decision